Evaluating Visual Cues for Future Airborne Surveillance Using Simulated Augmented Reality Displays - Barbotin, Nicolas; Baumeister, James; Cunningham, Andrew; Duval, Thierry; Grisvard, Olivier; Thomas, Bruce H. (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2022)
This work explores the interaction between Augmented Reality (AR) and eye accommodation for airborne surveillance by simulating AR environments in Virtual Reality (VR). We simulate the AR display as displays with the capabilities needed for airborne surveillance are limited and because it would be hazardous to experiment directly on surveillance aircraft. While there is precedent for simulating AR in a VR environment, our study account for two of the physical and physiological aspects of AR: we factor in the focal plane of the AR technology and simulate the eye accommodation reflex of the user to provide focus. We ran a study with 24 participants examining AR cues to support visual search. We also compare the effects of having secondary tasks (that surveillance operators are normally responsible for) directly on the observation window using AR. Our results show that the effectiveness of the AR cues is dependent on the modality of the secondary task. We also found that, under certain situations, operators' performances for the search task are improved if the focal plane of the AR display is at the same distance as subsequent search targets.